Full Bridge DC/DC Converter with Zero Current Switching Synchronous Rectification for Auxiliary Power Units - Sun, Zhe (My University, 2014)
Auxiliary power unit (APU) is a device that provides non-propulsion power in vehicles. In conventional commercial vehicles, APU is usually an alternator. For hybrid electric vehicles (HEVs) and electric vehicles (EVs), APU is a DC/DC converter. This APU provides power from the high voltage (HV) DC battery to the low voltage (LV) DC battery. The input side of the APU is the HV battery, which also provides power for the traction motor. The output side of the APU is the LV battery, which provides power for the electrical control systems and other electronic devices. Therefore, the design of the APU greatly impacts the operation and overall efficiency of the vehicle. The design challenges of APU include large output current, strict efficiency requirement and low electromagnetic interference (EMI). In this thesis, a phase shifted full bridge (PSFB) DC/DC converter with current doubler synchronous rectifier is proposed for APU applications. The proposed converter is able to endure large output current with low power loss. In addition, soft switching is applied to the converter based on the load conditions. This can effectively reduce EMI and improve converter efficiency. Detailed converter operating principles and design considerations are described. To further improve the converter efficiency, a zero current switching (ZCS) synchronous rectification (SR) control scheme is proposed. The proposed control scheme maximizes the SR MOSFET on-time and, therefore, reduces MOSFET body diode conduction loss. The proposed control scheme is verified by experimental results with a 2.4 kW, 100 kHz prototype.